2012
DOI: 10.1029/2011jg001724
|View full text |Cite
|
Sign up to set email alerts
|

Dust supply varies with sagebrush microsites and time since burning in experimental erosion events

Abstract: Wind erosion and large dust plumes are an increasingly important attribute in cold‐desert rangelands, particularly as wildfire increases. Fire reduces vegetation, which increases erosivity. Whether sediment supply increases after fire has not been determined in this environment. We asked how sediment supply varied among sites burned 2‐months to 5‐years previously, in comparison to unburned sagebrush steppe, across 500 km of southern Idaho, USA. We measured potential dust emissions (PM10, particles <10μm diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 91 publications
(132 reference statements)
3
20
0
Order By: Relevance
“…The REE tracer analysis of wind‐borne sediments from the burned replicate plots indicates that the Q is primarily composed of particles from the bare and shrub microsites (Figure b). These shrub microsites were found to be the most active sediment sources following the fire, which corroborates experiments based on different methods in other burned desert shrublands (Sankey, Germino, & Glenn, ). Greater enrichment of shrub tracers in grass microsites than vice versa indicates that the grass microsites became a significant sediment sink following the fire (Figure ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The REE tracer analysis of wind‐borne sediments from the burned replicate plots indicates that the Q is primarily composed of particles from the bare and shrub microsites (Figure b). These shrub microsites were found to be the most active sediment sources following the fire, which corroborates experiments based on different methods in other burned desert shrublands (Sankey, Germino, & Glenn, ). Greater enrichment of shrub tracers in grass microsites than vice versa indicates that the grass microsites became a significant sediment sink following the fire (Figure ).…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, burning of vegetative biomass at the surface can induce soil water repellency, which has been shown to enhance postfire soil erosion by decreasing the interparticle forces due to moisture in soils (DeBano, ; Ravi et al, , ). Recent studies using wind tunnels and small‐scale field experiments have qualitatively demonstrated that in shrublands and shrub‐grass transition zones fires can enhance soil erosion under raised shrub vegetated microsites (i.e., small‐scale patches representing the different surface cover types) and result in some level of sediment redistribution to the deflated interspaces (Ravi et al, ; Sankey, Germino, & Glenn, ; Sankey, Germino, Sankey, & Hoover, ; Sankey, Ravi, et al, ; White et al, ). Modeling studies have indicated that shrub recruitment and growth at an early stage of encroachment can be controlled with lower grazing intensity and recurrent prescribed or natural fires (Ravi & D'Odorico, ).…”
Section: Introductionmentioning
confidence: 99%
“…There is also a strong variability of soils in semi-arid ecosystems associated with the location of individual plants (Charley and West 1975, Burke et al 1989a, Burke et al 1989b, Hook et al 1991, Schlesinger et al 1996, Sankey et al 2012a). This fine-scale heterogeneity in soil organic matter, which is concentrated under individual shrubs relative to interspaces, is a well-recognized feature of sagebrush ecosystems, with indications that it is responsive to changes in ecosystem management (Burke et al 1987, Sankey et al 2012b.…”
Section: Introductionmentioning
confidence: 99%
“…Field reconnaissance observed considerable redistribution of wind‐detached sediment and organic debris into hillslope hollows or swales throughout MCEW over the first month after the fire (Figure ; Vega, ). Sediment and debris redistribution by aeolian processes during this period were not quantified for logistical reasons, but field‐observed trends in wind erosion and subsequent sediment and debris deposition were consistent with those reported for the immediate post‐fire period in numerous wind erosion studies of sagebrush steppe (Sankey et al, , , , ; Wagenbrenner et al, ).…”
Section: Methodsmentioning
confidence: 99%